2022
DOI: 10.1001/jamanetworkopen.2022.6114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient-Specific Human Leukocyte Antigen Genomic Loss at Relapse After Antithymocyte Globulin–Based T-Cell–Replete Haploidentical Hematopoietic Stem Cell Transplant

Abstract: IMPORTANCE Patient-specific human leukocyte antigen (HLA) genomic loss (HLA loss) is one of the reputed mechanisms of leukemia immune escape and relapse after haploidentical hematopoietic stem cell transplant (HSCT). However, clinical characteristics and prognosis of this distinct relapse type in the setting of haploidentical HSCT based on antithymocyte globulin (ATG) T-cell-replete conditioning are still unknown, especially for patients with lymphoid leukemia. OBJECTIVE To identify the incidence of and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Crucitti et al and Wang et al suggested that the HLA allele matching degree is an independent risk factor of HLA loss. 7,18 Wu et al reported that the incidence of HLA loss in patients with myeloid leukaemia undergoing haplo-HSCT was up to 54.7% (29/53), 19 and patients treated by HLA mismatched HSCT were more vulnerable to develop HLA loss relapse than those treated by HLA matched HSCT. Those results were in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Crucitti et al and Wang et al suggested that the HLA allele matching degree is an independent risk factor of HLA loss. 7,18 Wu et al reported that the incidence of HLA loss in patients with myeloid leukaemia undergoing haplo-HSCT was up to 54.7% (29/53), 19 and patients treated by HLA mismatched HSCT were more vulnerable to develop HLA loss relapse than those treated by HLA matched HSCT. Those results were in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [ 7 ] all patients received either a myeloablative busulfan/cyclophosphamide-based conditioning regimen or a reduced intensity regimen consisting of fludarabine/busulfan. Antithymocyte globulin-Genzyme (ATG-G) or anti-thymocyte globulin Fresenius (ATG-F) was applied as preparation for haplo-HSCT.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of HLA antigens reduces the efficacy of the GVL effect and favors the immune escape of AML cells. In haploidentical HSCT, as there is no incompatible target to stimulate alloreactivity, the GVL effect remains low[ 168 , 169 ]. Wu et al [ 169 ] analyzed nearly 800 cases of AML and ALL that were subjected, following an ATG T cell-replete conditioning regimen, to haploidentical HSCT and delineated that relapse occurred faster in AML patients who experienced loss of HLA antigens vs those who did not (223 d vs 321 d, P = 0.03).…”
Section: Intervention and Treatment Strategies For Post-allo-hsct Rel...mentioning
confidence: 99%
“…In haploidentical HSCT, as there is no incompatible target to stimulate alloreactivity, the GVL effect remains low[ 168 , 169 ]. Wu et al [ 169 ] analyzed nearly 800 cases of AML and ALL that were subjected, following an ATG T cell-replete conditioning regimen, to haploidentical HSCT and delineated that relapse occurred faster in AML patients who experienced loss of HLA antigens vs those who did not (223 d vs 321 d, P = 0.03). The factors linked with HLA loss in AML were aGVHD (odds ratio = 4.84) and body mass index < 18.5 kg/m 2 (odds ratio = 0.10).…”
Section: Intervention and Treatment Strategies For Post-allo-hsct Rel...mentioning
confidence: 99%
See 1 more Smart Citation